Deaf Social Media Influencers' Content Analysis: Creating Engagement with Educational Content - Santi Setyaningsih; Prahastiwi Utari; Ignatius Agung Satyawan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Social media has evolved into a communication tool that promotes inclusivity, allowing persons with disabilities to share a variety of messages with their audiences. @jennifernatalie_ is a deaf Social Media Influencer (SMI) who uses TikTok to share sign language-related educational content. Despite her difficulty talking verbally, @jennifernatalie_ is capable of generating quite high levels of engagement with her followers. The goal of this study is to analyze @jennifernatalie_'s sign language educational content in terms of creating engagement with followers along five characteristics that support SMI communications. This study used a qualitative study content analysis methodology. The research data was gathered by assessing the content of short videos on TikTok @jennifernatalie_ and enhanced by literature reviews from various sources relevant to the research issues. The findings showed that @jennifernatalie_ was capable of presenting the five dimensions of SMI communications to generate engagement through her educational TikTok posts.